Moot Court for teaching – learning of court procedures in MBBS students in central region of India - an Educational interventional study. (Indian Journal of Forensic Medicine & Toxicology, 2025)
BackgroundAs a doctor we all need to attend the court of law either as a first treating doctor or treating doctor of a speciality or as subject expert as an expert witness.                       There are many incidents reported and also we experience as a part of society and medical institutes, where a doctor tries to avoid attending a case having legal implication either poisoning or some injury by any means so that he/she can avoid attending the court.   Usually it’s not because the doctor feels incompetent in treatment but most of the time it is the apprehension to attend the court.    It was also observed that when a doctor goes to court for a few times they will become more confidant and comfortable, but first experience remains more or less same. It gave us an ideas that if Indian medical graduates, can get some practical experienceduring MBBS (even in simulation situation) e.g. “moot court1” with the theory class on legal procedure, this apprehension can be removed or minimised and in future they will not be hesitant to attend cases with legal implication.Primary Objective:      Students will get more practical knowledge about court procedures.     Secondary Objectives:• Future IMG will become more confident in court• Future IMG will not hesitate to attend medico-legal cases in future during their professional life.• Introducing moot court to the students as simulation technique for the court procedure.• To assess the effectiveness of moot court in comparison of didactic lecture on court procedure by comparing pre and post-test about the topic.Methodology - It is an Educational interventional study.Convenient sample technique was used for sampling method, in which 130 students of Phase III part 1 MBBS, of MIMS & R, Bhopal (MP), participated. Informed consent was obtained. Data collected by pre and post-test and paired t-test was used to analyse them. Results - On observing in pre and post-test of the sample size 99 and using paired samples t-test (with 95% Confidence Interval of the Difference) mean value in post-test increased from 13.63 to 17.34, showed the improvement in the knowledge of the students about topic. In the study Std. Deviation decreased from 3.14 to 2.47. Std. Error Mean decreased from 0.32 to 0.25. In the study t-value is 12.1770 and P value is
Keywords: Court Procedure, Medicolegal cases, Moot Court.